2013
DOI: 10.2527/jas.2011-4287
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary ractopamine HCl and L-carnitine on finishing pigs: II. Carcass characteristics and meat quality1,2

Abstract: Three experiments using 1,356 pigs (C22 × 336 PIC) were conducted to determine the interactive effects of dietary L-carnitine and ractopamine hydrochloride (RAC) on carcass characteristics and meat quality of finishing pigs. Experiments were arranged as factorials with main effects of L-carnitine and RAC; L-carnitine levels were 0, 25, or 50 mg/kg in Exp. 1 and 2 and 0 or 50 mg/kg in Exp. 3, and RAC levels of 0, 5, or 10 mg/kg in Exp. 1 and 0 or 10 mg/kg in Exp. 2 and 3. Dietary L-carnitine was fed from 38 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The lack of a RAC effect on ultimate pH reported here is in agreement with studies examining the RAC response on numerous variables including breed (Stoller et al, 2003), heavy weight/late finishing pigs (Fernández-Duenas et al, 2008;Kutzler et al, 2011), or pigs raised under commercial conditions (Athayde et al, 2012). Of the numerous studies that have found a significant effect of RAC on ultimate pH (Carr et al, 2005;Apple et al, 2008;James et al, 2013), pH values were increased by 0.07 to 0.08. The lack of 24-h pH effects indicates that our treatments did not affect postmortem ultimate pH; therefore, this demonstrates that the meat quality attributes measured in the study are independent of treatment catalyzed ultimate pH differences.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of a RAC effect on ultimate pH reported here is in agreement with studies examining the RAC response on numerous variables including breed (Stoller et al, 2003), heavy weight/late finishing pigs (Fernández-Duenas et al, 2008;Kutzler et al, 2011), or pigs raised under commercial conditions (Athayde et al, 2012). Of the numerous studies that have found a significant effect of RAC on ultimate pH (Carr et al, 2005;Apple et al, 2008;James et al, 2013), pH values were increased by 0.07 to 0.08. The lack of 24-h pH effects indicates that our treatments did not affect postmortem ultimate pH; therefore, this demonstrates that the meat quality attributes measured in the study are independent of treatment catalyzed ultimate pH differences.…”
Section: Discussionsupporting
confidence: 90%
“…percentage lean. In the companion paper of the present paper (James et al, 2013), there were tendencies for pigs in Exp. 1, 2, and 3 to have increased percentage lean and decreased 10th rib fat depth.…”
Section: Discussionmentioning
confidence: 65%
“…At the end of Exp. 1, 2, and 3, pigs were slaughtered to evaluate carcass characteristics and meat quality (James et al, 2013). All dietary nutrients were formulated to meet or exceed recommended requirement estimates (NRC, 1998).…”
Section: Generalmentioning
confidence: 99%
“…Inspired by the function of L-carnitine, some studies have investigated the effect of L-carnitine as a potential feed additive in pigs. In finishing pigs fed ractopamine hydrochloride, supplementation of L-carnitine decreased the L∗ value and increased the ratio of the a∗ value to b∗ value ( James et al., 2013 ). Moreover, without ractopamine hydrochloride supplementation, L-carnitine decreased the drip loss and tended to increase pH 24h independently ( James et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%